Fifth Generation Warfare and Cyber Conflict: Pakistan’s Vulnerability to Digital Terrorism - Saeed Ahmed (ASIAN Journal of International Peace & Security (AJIPS), 2024)
The rise of digital terrorism and the increasing use of cyber warfare techniques pose significant threats to Pakistan’s national security. This research explores the evolving landscape of Fifth Generation Warfare (5GW) and its implications for state stability, focusing on the role of disinformation, cyber espionage, and extremist digital mobilization. The core issue under examination is how state and non-state actors leverage digital platforms to manipulate public perception, destabilize institutions, and undermine national security frameworks. To analyze these threats, the study applies Hybrid Warfare Theory (HWT) and Cyber Conflict Theory (CCT) as conceptual frameworks. The research employs a qualitative methodology, incorporating a thematic analysis of policy reports, government records, cybersecurity assessments, and expert interviews. Additionally, a comparative approach is used to assess how internal and external cyber threats interact, particularly within the Pakistan-India geopolitical rivalry and the role of transnational terrorist networks in online radicalization. Findings reveal critical gaps in Pakistan’s cybersecurity policies, institutional preparedness, and civil-military coordination, highlighting vulnerabilities in both digital governance and crisis response mechanisms. The study concludes that a robust national cybersecurity strategy, enhanced cyber diplomacy, and AI-driven threat detection mechanisms are essential for mitigating digital terrorism.